2021
DOI: 10.3389/fonc.2021.555331
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Biomarkers for Early Stage Non-Small Cell Lung Carcinoma Detection: Supplementation to Low‐Dose Computed Tomography

Abstract: Lung cancer is currently the leading cause of cancer death in both developing and developed countries. Given that lung cancer has poor prognosis in later stages, it is essential to achieve an early diagnosis to maximize patients’ overall survival. Non-small cell lung cancer (NSCLC) is the most common form of primary lung cancer in both smokers and non-smokers. The current standard screening method, low‐dose computed tomography (LDCT), is the only radiological method that demonstrates to have mortality benefits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 107 publications
(129 reference statements)
0
7
1
Order By: Relevance
“…Although several biomarkers have been suggested for the diagnosis and prognosis of LC, in the era of precision medicine, there is still a need to identify “tailored markers” that can be proposed in clinical setting for early diagnosis, prognosis and targeted therapy [ 19 ]. Additionally, it would be beneficial to identify diagnostic biomarkers able to optimize the current LDCT protocols, allowing, for example, the identification of the false positives, as well as the stratification of CT-positive subjects [ 20 , 21 ]. Among the challenges currently faced by research on LC biomarker development, there is the need for a deeper knowledge of lung carcinogenesis at both molecular and cellular levels.…”
Section: Introductionmentioning
confidence: 99%
“…Although several biomarkers have been suggested for the diagnosis and prognosis of LC, in the era of precision medicine, there is still a need to identify “tailored markers” that can be proposed in clinical setting for early diagnosis, prognosis and targeted therapy [ 19 ]. Additionally, it would be beneficial to identify diagnostic biomarkers able to optimize the current LDCT protocols, allowing, for example, the identification of the false positives, as well as the stratification of CT-positive subjects [ 20 , 21 ]. Among the challenges currently faced by research on LC biomarker development, there is the need for a deeper knowledge of lung carcinogenesis at both molecular and cellular levels.…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs have emerged as important diagnostic and prognostic biomarkers and therapeutic targets in cancer treatment due to their functional involvement in gene and protein regulation and intracellular signaling [ 52 , 53 ]. MiRNA biomarkers are promising for the early detection of NSCLC supplementing low-dose CT screening [ 54 ] and the prognosis of advanced NSCLC patients treated with immunotherapy [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, NSCLC has a high mortality rate, and the 5-year survival rate of these patients remain challenging (54)(55)(56)(57). Despite advancements in early detection and treatment of NSCLC, the identification of molecular markers associated with patient survival is still necessary (53,(58)(59)(60). Multiple studies have demonstrated that FOXD3-AS1 is overexpressed in NSCLC tissues and cell lines (H1299, A549 and SPC-A1 cells) (24,(26)(27)(28).…”
Section: Lung Cancermentioning
confidence: 99%